Analisis kesulitan siswa dalam menghadapi soal aritmatika sosial - Wahyuni, Indah; Hatiningwan, Eko Prastya; Anam, Khoirul; Anggraini, Sherly Shela; Mardiya, Raudatul (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aim of this research is to provide an explanation of the various types of difficulties faced by students when working on social arithmetic story problems and to analyze their components. The method used to collect this information is descriptive method. The research subjects were students of Jenggawah Middle School class VIII J for the 2022/2023 academic year. The study was used to measure how difficult it was for students to solve word problems about social arithmetic material with two questions that corresponded to indicators of their understanding of mathematical concepts. After the data was collected, the researcher analyzed the results of working on arithmetic story questions that had been done by Jenggawah Middle School students in class VIII J. The research results showed that students often made mistakes in social arithmetic questions, especially students who did not understand the material, did not understand the questions, and difficulty in operating the formula.